(untitled) (Journal of Forensic Medicine & Toxicology, 2011)
Acid decomposition / digestion procedures are used for quantitative / qualitative determination of metals in different matrixes. Basic purpose of digestion for different samples is to complete the transfer of analytes into solution, which is essential requirement for AAS, ICP, voltammetry etc. Acid digestion is either open digestion or closed digestion. Open digestion has certain disadvantages such as high acid consumption, more time taking, poor digestion quality, loss of volatile elements such as mercury (Hg), lead (Pb) and high contamination risk over closed digestion. Applications of microwave digester are found in diverse fields such as forensic science, pharmaceuticals, food and agriculture, biological and clinical chemistry, environmental chemistry and many others. This paper is in continuation of Forensic Instrumental technique series VI, Atomic Absorption Spectrometry – A Review, Journal of Forensic Medicine & Toxicology Vol. 27 No. 2, July-Dec 2010.